Intracranial Haemorrhage due to Minor Trauma in a Patient with Idiopathic Thrombocytopenic Purpura- A Case Report (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: Intracranial haemorrhage (ICH) is a rare but the most dangerous complication of idiopathic thrombocytopenic purpura (ITP) which is usually fatal. ITP is caused by autoantibodies to platelet which can be demonstrated in plasma. Case-Report: A 32 years old male patient sustained minor trauma around his head, following which he developed features of raised intracranial pressure including headache, vomiting and loss of consciousness. On examination Glasgow Coma Scale was 7/15 (E2, M3, V2), left pupil was moderately dilated, there was bilateral papilloedema and haemorrhagic spots on the left sided retina. CT scan of the head showed significant intracranial haemorrhage. Laboratory investigation showed anaemia and thrombocytopenia with platelet count 40X109/L. All the relevant causes of thrombocytopenia were excluded and the diagnosis of ITP was established. Intracranial haemorrhage was managed conservatively without surgical intervention. ITP was managed with splenectomy on 12th day following a period of therapy with steroids, transfusion of packed cell and platelet concentrates. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18740 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 115-117